Process parameters optimization for eco-friendly high strength sandcrete block using Taguchi method. Issue 6 (June 2020) - Ikeagwuani, Chijioke Christopher; Nwonu, Donald Chimobi; Ugwu, Chiagoziem Kanayo; Agu, Chukwudi Cajethan
Abstract: The need for developing sustainable cement-based materials is crucial for the prevention of environmental degradation and promotion of sustainable technologies. In the present study, a sustainable cement-based material was developed for sandcrete block production using coconut shell ash (CSA). The product development was executed using the Taguchi robust design approach, in which an L18 mixed level orthogonal array was adopted. The process parameters investigated were the end-web to center-web (E/C) ratio of the sandcrete block, water-cement (W/C) ratio and CSA content. The evaluated responses include the compressive strength (CS), bulk density (BD) and water absorption (WA). The result obtained showed that for the CS, all the process parameters had a statistically significant effect at 0.05 alpha level, while only the W/C ratio had a statistically significant effect on the BD and WA. The optimal settings of the process parameters for CS and BD were obtained at E/C ratio of 1:2, W/C ratio of 0.65 and CSA content of 5% while that for WA was obtained at E/C ratio of 1:1, W/C ratio of 0.65 and CSA content of 20%. The developed sandcrete blocks are suitable for load-bearing masonry units and areas with moisture exposure. Abstract : Civil engineering; Construction Engineering; Concrete Technology; Cement Additive; Cement; bulk density; Compressive strength; Optimization; Sandcrete blocks; Taguchi approach; water absorption